Carriage of methicillin‐resistant staphylococci by healthy companion animals in the US. (15th April 2014) - Davis, J.A.; Jackson, C.R.; Fedorka‐Cray, P.J.; Barrett, J.B.; Brousse, J.H.; Gustafson, J.; Kucher, M.
Abstract Antimicrobial‐resistant staphylococci have been associated with wounded or ill companion animals, but little is known about the prevalence of resistant staphylococci among healthy animals. In this study, 276 healthy dogs and cats from veterinary clinics were tested for the presence of antimicrobial‐resistant Staphylococcus spp. Isolates were tested for antimicrobial susceptibility and the presence of select resistance genes, and typed using Pulsed‐Field Gel Electrophoresis (PFGE). Staphylococcus aureus and Staphylococcus pseudintermedius were also characterized using multilocus sequence typing (MLST), spa typing and SCCmec typing. Approximately 5% (14/276) of the animals were positive by enrichment for five species of staphylococci [Staph. aureus (n = 11), Staph. pseudintermedius (n = 4), Staphylococcus sciuri (n = 6), Staphylococcus simulans (n = 1) and Staphylococcus warneri (n = 1)]. Seventy‐eight per cent (18/23) of staphylococci were resistant to oxacillin and also multidrug resistant (resistance to ≥ 2 antimicrobials). All Staph. aureus isolates were mecA+ and blaZ+, SCCmec type II, spa type t002, ST5 and clonal using PFGE. Staphylococcus pseudintermedius were SCCmec type IV or V, spa type t06 and ST170; two of the isolates were pvl+. These results suggest that healthy companion animals may be a reservoir of multidrug‐resistant staphylococci, which may be transferred to owners and others who handle companion animals. Significance and Impact of the Study In this study, antimicrobial‐resistant coagulase‐negative and coagulase‐positive staphylococci were isolated from various body sites on healthy dogs and cats. Resistance to 14 antimicrobials was observed including resistance to oxacillin; the majority of staphylococci were also multidrug resistant. Results from this study suggest that healthy dogs and cats may act as reservoirs of antimicrobial‐resistant bacteria that may be transferred to people by simple interaction with the animals. Such carriage poses an underlying risk of infection, which should be considered during handling of healthy dogs and cats by pet owners and veterinary personnel.